Pengaruh Self Management pada Pasien Hipertensi: Sebuah Tinjauan Sistematis - Yofa Anggriani Utama (Universitas Batanghari Jambi, 2023)
Hypertension is a non communicable disease which is one of the main causes of disability and death in the world. The world health organization World Health Organization (WHO), estimates that currently the global prevalence of hypertension is 22% of the total world population. Of these sufferers, only less than one – fifth made efforts to control blood pressure. Until now, hypertension is still a challenge spread across Indonesia. The purpose of this study was to determine the effect of self management on hypertensive patients. The research design included in this systematic review uses a quantitative research design. Based on the results of a systematic review, it design was found that there was an effect of self management on hypertensive patients, to improve self managemen, motivation and support from the family and health promotion are needed in order to achieve optimal treatment and control of blood pressure.